International economic papers - International economic association; International Economic Association (New York : Macmillan and Co., 1959)
The first two articles in this volume, widely separated though they are in the stream of the history of economic thought, will hope once more make case for the inclusion of contributions of historical interest.
Volume 9.
Includes bibliographical footnotes and index.
hza 28/01/2019
Loans
Keywords: Economics